Scheme for Financial Assistance to Dance, Drama, and Theatre Ensembles - A Quick Study 1993-94 - Planning Commission (Planning Commission, 1994)
With a view to preserve, promote, and disseminate art and culture in the country, Government of India has been making sustained efforts over the different plan periods and initiated a number of programmes, schemes, and projects for this purpose. Inspite of such efforts it was felt that art and culture in the country, especially performing arts were languishing for want of financial assistance from the Government of India on sustained basis, as during the three Five Year Plan periods (1951-66) sufficient funds were not allocated for cultural and other activities because of the demands from other priority sectors.
Programme Evaluation Organisation
Planning Commission Government of India